Do public service motivation and organizational processes influence job satisfaction and organizational commitment? A comparative study in public and private organizations - Park, Mingean; Lee, Byung Ho (Chinese Public Administration Review, 2023)
This study investigates the impact of public service motivation (PSM) on job satisfaction and organizational commitment while controlling for four types of organizational processes and individual attributes. Furthermore, it tests whether PSM is unique to public organizations by comparing public and private organizations. We use individual-level microdata from the “Survey on the Comparison of Public and Private Organizations in Korea” to address these issues. The sample for this survey, conducted by the Korea Institute of Public Administration (KIPA) in 2014, included 2,047 participants, consisting of 1,000 civil servants and 1,047 private sector employees. First, we find that PSM positively impacts job-related work outcomes such as job satisfaction and organizational commitment in both public and private organizations. Second, we show that public sector employees have significantly higher levels of PSM than their private sector counterparts. These results indicate the importance of PSM in public administration and have a policy implication that public organizations need to design effective methods to improve the PSM levels of their employees. Third, both PSM and organizational processes jointly influence job satisfaction and organizational commitment; however, their effects differ between the public and private sectors. In conclusion, our research confirms that PSM is a crucial determinant of public organization characteristics in the East Asian context, highlighting its significance for public administration.
Keywords: Job satisfaction; organizational commitment; organizational process; public service motivation; South Korea